Water Resources Management for Sustainable Development: Study With Reference to Indian Context: Challenges and Solutions for Water Resources Management in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Water is one of life's most significant natural commodities. In agriculture output, its growth and management play a crucial part. In order to minimize poverty, maintain the climate and sustained economic growth, adaptation of water resources is crucial. With population, urbanization and industrialization rapidly increasing, there is an ever-increasing demand for water to meet different requirements. Therefore, we face many problems in the water market, including reducing the supply of per capita water, the decrease in groundwater table in many regions, and the accumulation of saltwater in coastal aquifers. Surface and ground water quality is also deteriorating as pollutant loads from different sources increase. The supply and distribution of water supplies can also be negatively impacted by climate change. This article provides an overview of relevant problems related to Indian water resources development and management.